Sosialisasi Ecobrick sebagai Solusi atas Masalah Pengolahan Sampah Plastik di Desa Mojowangi, Jombang, Jawa Timur - Nadiza Rahma Talitanahda; Ainurrohmah, Syafika; Bunga Annisa; Dhian Satria Yudha Kartika (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Mojowangi Village, Mojowarno District, Jombang Regency, is a village that has strong cultural potential. However, this village also faces environmental weaknesses in the form of increasingly worrying plastic waste problems. Ecobrick socialization in Mojowangi Village is a very important effort to overcome the problem of plastic waste. Using a participatory method, this activity involves PKK mothers in making ecobricks, namely plastic bottles filled with solid plastic waste. The main objective is to increase community awareness and skills in sustainable plastic waste management. This activity also contributes to achieving the Sustainable Development Goals (SDGs), especially goals number 11 (Sustainable Cities and Settlements) and number 12 (Responsible Consumption and Production). The results of the activity show an increase in community awareness, skills, and active participation, as well as opening up new economic opportunities for the community. Thus, this activity not only has a positive impact on the environment but can also improve the economy of the local community